Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Petani Padi di Kecamatan Babirik Kabupaten Hulu Sungai Utara - Reza, Muhammad; Effendi, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was designed to (1) calculate land productivity; (2) to analyze effect of the land area, labor, seeds and fertilizers on the income of rice farmers; (3) find out the most dominant factors affecting the income of rice farmers. This research took the case study area in Babirik Sub-district, HSU disctrict. The data source is primary, obtained via questionnaires will be analyzed with multiple regression linier which will be tested through the f-test and the t-test. This research found that land productivity was up to standard. Then simultaneously land area, labor, seeds and fertilizers had an significant effect. Land area is the most dominant factor affecting the income of rice farmers.